2005
DOI: 10.1007/s11095-004-1196-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lipid Nanocapsules Composition on Their Aptness to Freeze-Drying

Abstract: This paper is a contribution to methodological development of the formulation of lipid nanocapsules, with a special emphasis on the aptness to freeze-drying and the stability under storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…33 Contrary to previous observations on the LNC-freeze-drying process in the presence of trehalose, no modification of size was observed, despite the absence of lecithin, and THP-T80-LNCs can be freezedried. 34 This observation was confirmed by Saliou et al who demonstrated the interest of PEG chains to act as stabilizers during freeze-drying. 15 Freeze-drying conserved the physical characteristics of THP-T80-LNCs and preserved the total decitabine concentration, despite a residual content of water (25% of the initial quantity), probably insufficient to hydrolyze decitabine during storage.…”
mentioning
confidence: 66%
“…33 Contrary to previous observations on the LNC-freeze-drying process in the presence of trehalose, no modification of size was observed, despite the absence of lecithin, and THP-T80-LNCs can be freezedried. 34 This observation was confirmed by Saliou et al who demonstrated the interest of PEG chains to act as stabilizers during freeze-drying. 15 Freeze-drying conserved the physical characteristics of THP-T80-LNCs and preserved the total decitabine concentration, despite a residual content of water (25% of the initial quantity), probably insufficient to hydrolyze decitabine during storage.…”
mentioning
confidence: 66%
“…When lecithin alone was employed at low concentrations the phospholipid monolayer was not stable enough to prevent particle aggregation (37,38). At higher concentrations, lecithin is known to crystallize during freeze drying and affect the physical characteristics of the freeze-dried cake (39). However, when combined with water-soluble non-ionic surfactant DHC DHC Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This instability resulted from the release of paclitaxel from the lipid nanocapsules and the formation of crystals of paclitaxel in its external aqueous phase because of its very low aqueous solubility. To overcome this problem, lyophilization of paclitaxel-loaded LNC could be carried out in the presence of a cryoprotectant such as trehalose, which seems to be the best additive for the lyophilization of LNC (27).…”
Section: Formulationmentioning
confidence: 99%